The young stellar content of the giant H II regions M 8, G333.6−0.2, and NGC 6357 with VLT/KMOS - Ramírez-Tannus, María Claudia; Poorta, J.; Bik, Arjan; Kaper, L.; Koter, A. de; Ridder, J. De; Beuther, Henrik; Brandner, W.; Davies, B.; Gennaro, Mario; Guo, D.; Henning, Thomas; et al. (Astronomy and astrophysics, 2020)
The identification and characterisation of populations of young massive stars in (giant) H II regions provides important constraints on (i) the formation process of massive stars and their early feedback on the environment, and (ii) the initial conditions for population synthesis models predicting the evolution of ensembles of stars.Aims. We identify and characterise the stellar populations of the following young giant H II regions: M 8, G333.6−0.2, and NGC 6357.Methods. We have acquired H- and K-band spectra of around 200 stars using the K-band Multi Object Spectrograph on the ESO Very Large Telescope. The targets for M 8 and NGC 6357 were selected from the Massive Young Star-Forming Complex Study in Infrared and X-ray (MYStIX), which combines X-ray observations with near-infrared (NIR) and mid-infrared data. For G333.6−0.2, the sample selection is based on the NIR colours combined with X-ray data. We introduce an automatic spectral classification method in order to obtain temperatures and luminosities for the observed stars. We analysed the stellar populations using their photometric, astrometric, and spectroscopic properties and compared the position of the stars in the Hertzprung-Russell diagram with stellar evolution models to constrain their ages and mass ranges.Results. We confirm the presence of candidate ionising sources in the three regions and report new ones, including the first spectroscopically identified O stars in G333.6−0.2. In M 8 and NGC 6357, two populations are identified: (i) OB main-sequence stars (M > 5 M⊙) and (ii) pre-main sequence stars (M ≈ 0.5 − 5 M⊙). The ages of the clusters are ∼1−3 Myr, < 3 Myr, and ∼0.5−3 Myr for M 8, G333.6−0.2, and NGC 6357, respectively. We show that MYStIX selected targets have > 90% probability of being members of the H II region, whereas a selection based on NIR colours leads to a membership probability of only ∼70%.
Gesehen am 19.05.2020